2022
DOI: 10.1088/2631-7990/aca8da
|View full text |Cite
|
Sign up to set email alerts
|

Novel Ni3S4/NiS/NC composite with multiple heterojunctions synthesized through space-confined effect for high-performance supercapacitors

Abstract: The construction of heterojunctions in composite materials to optimize the electronic structures and active sites of energy materials is considered to be the promising strategy for the fabrication of high performance electrochemical energy devices. In this paper, a one-step, easy processing and cost-effective techniques for generating heterojunctions of the composite materials are successfully developed. The composite containing Ni3S4, NiS, and N-doped amorphous carbon (abbreviated as Ni3S4/NiS/NC) with multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…That is to say, there are two pairs of redox peaks, which in turn correspond to the reversible redox reaction between Ni 2+ and Ni 3+ , and Ni 3+ and Ni 4+ . 23,24 With the increase of the scan rates, the concentration polarization and electrochemical polarization gradually shift the position of the redox peaks to both ends (Fig. 4a).…”
Section: Resultsmentioning
confidence: 96%
“…That is to say, there are two pairs of redox peaks, which in turn correspond to the reversible redox reaction between Ni 2+ and Ni 3+ , and Ni 3+ and Ni 4+ . 23,24 With the increase of the scan rates, the concentration polarization and electrochemical polarization gradually shift the position of the redox peaks to both ends (Fig. 4a).…”
Section: Resultsmentioning
confidence: 96%
“…4c, the Ni 2p spectrum consists of two pairs of satellite peaks at 860.0 and 877.0 eV and 862.8 and 879.9 eV and two pairs of spin–orbit doublet peaks corresponding to Ni 2p 3/2 and Ni 2p 1/2 of Ni 2+ (852.1 and 869.4 eV) and Ni 3+ (855.6 and 873.4 eV) Ni 2+ and Ni 3+ , respectively, distributed in Ni 3 S 4 and Ni x S 6 . 38,39 In Fig. 4d, the S 2p spectrum was analyzed, revealing four distinct peaks, with the peaks located at 160.0 and 161.1 eV corresponding to S 2p 3/2 and S 2p 1/2 of S 2− , respectively, and the other two peaks at 162.2 and 167.7 eV are associated with the presence of S–C bonds and the oxidation of Ni 3 S 4 and Ni x S 6 , 40 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the electrochemical characteristics of composite materials are usually superior to those of single materials. 25 Meanwhile, the composite materials can use the benefits of two materials and intentionally combine them into a hierarchical structure to compensate for drawbacks in single structures. 26 Some published works have indicated that the electrochemical performances of metal oxides, sulfides and hydroxides (NiCo 2 O 4 @Ni(OH) 2 , 27 MnCo 2 O 4 @Ni 3 S 2 , 28 NiCo 2 O 4 @NiCo 2 S 4 , 29 NiCo 2 O 4 @Ni–S, 30 or NiCo 2 O 4 @NiCo-LDH 31 ) are better than those of single metal oxides.…”
Section: Introductionmentioning
confidence: 99%